2019
DOI: 10.1038/s41598-019-53769-z
|View full text |Cite
|
Sign up to set email alerts
|

Wild specimens of sand fly phlebotomine Lutzomyia evansi, vector of leishmaniasis, show high abundance of Methylobacterium and natural carriage of Wolbachia and Cardinium types in the midgut microbiome

Abstract: Phlebotomine sand flies are remarkable vectors of several etiologic agents (virus, bacterial, trypanosomatid Leishmania), posing a heavy health burden for human populations mainly located at developing countries. Their intestinal microbiota is involved in a wide range of biological and physiological processes, and could exclude or facilitate such transmission of pathogens. In this study, we investigated the Eubacterial microbiome from digestive tracts of Lu. evansi adults structure using 16S rRNA gene sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 50 publications
2
26
0
Order By: Relevance
“…Our results showing the presence of Methylobacterium in females from colony and field substrate after the infection with L . infantum support the suggestion of [ 50 ], that Methylobacteriaceae remains in the sand fly midgut in the presence of Leishmania infections. Methylobacteriacae were exceptionally extant in poorly developing larvae in sand flies reared on cashew leaf litter, so it would be worthwhile to explore whether the harmful effect is attributable to Methylobacterium or innate chemical properties of cashew leaves.…”
Section: Discussionsupporting
confidence: 87%
“…Our results showing the presence of Methylobacterium in females from colony and field substrate after the infection with L . infantum support the suggestion of [ 50 ], that Methylobacteriaceae remains in the sand fly midgut in the presence of Leishmania infections. Methylobacteriacae were exceptionally extant in poorly developing larvae in sand flies reared on cashew leaf litter, so it would be worthwhile to explore whether the harmful effect is attributable to Methylobacterium or innate chemical properties of cashew leaves.…”
Section: Discussionsupporting
confidence: 87%
“…The distinct composition of the bacterial community of P. papatasi was driven by three OTUs belonging to Spiroplasma and Wolbachia . These are common facultative endosymbionts of Phlebotomus [ 28 , 44 ], Lutzomyia [ 30 , 31 ] and other insects; it is now estimated that Wolbachia and Spiroplasma endosymbionts are present in up to 30% of all insects [ 45 ]. They are maternally inherited, and they affect host ecology, physiology and fitness [ 15 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sandfly gut microbiota can be modulated (i) by their feeding habits: larvae feeding on soil dead organic matter, while female adults get blood and sugar meals (plant-fed) and (ii) through interactions with transmitting parasites [ 26 , 27 ]. To date the gut microbiota of Phlebotomus sandflies has been studied using culture-dependent approaches [ 28 , 29 ], while recent studies on Lutzomyia longipalpis have used culture-independent approaches [ 30 , 31 ]. The gut bacterial community of sandflies is dominated by Proteobacteria and Firmicutes.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that previous findings on gut bacterial communities in female sand flies from South America were obtained using classic techniques for molecular ecology, such as denaturing gradient gel electrophoresis (DGGE), except for a recent study in which a microbiome analysis of the digestive tracts of Lu. evansi adults was performed using 16S rRNA gene sequence amplicon high-throughput sequencing (Illumina MiSeq) [ 44 ]. The use of high-throughput technology enables a large number of reads in a single run, thereby providing a greater sampling depth than other techniques [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results are partly in agreement with the findings of a recent meta-analysis of sand fly-associated bacteria, which revealed that more than 57% and 47% of identified bacteria belonged to the Proteobacteria phylum in New and Old World sand fly species, respectively [ 46 ]. Actinobacteria showed lower abundance [ 11 , 44 , 47 , 48 , 49 ]. Previous studies reported that the phylum Proteobacteria contributed to host nutrition by fixing atmospheric nitrogen [ 50 ].…”
Section: Discussionmentioning
confidence: 99%